SAT0240 Vagus nerve stimulation in patients with rheumatoid arthritis: two-year safety and efficacy. (12th June 2018) - Koopman, F. A.; Musters, A.; Backer, M. J.; Gerlag, D.; Miljko, S.; Grazio, S.; Sokolovic, S.; Levine, Y. A.; Chernoff, D.; de Vries, N.; Tak, P.-P.
Abstract : Background: Rheumatoid arthritis (RA) is a debilitating chronic disease with an unmet need for additional therapeutic approaches. Activating neuro-immune reflex pathways by stimulation of the vagus nerve (VNS) could represent a novel means of treating RA [1] and other immune-mediated inflammatory diseases. Last year we reported a 12-week proof-of-concept study using a VNS device, approved for drug-resistant epilepsy, showing reduction in the DAS28-CRP clinical disease activity score, with concomitant reductions in TNF and IL-6 levels [2]. Objectives: To understand the long term safety and efficacy of this novel treatment approach, we followed the patients in a 24 months long-term extension study and report on the safety and clinical efficacy data. Methods: VNS devices were implanted into 17 RA patients, mostly with insufficient response to multiple conventional and biologic disease-modifying antirheumatic drugs (DMARDs), on stable background of methotrexate (≤25 mg weekly) therapy. The devices electrically stimulated the vagus nerve, 1–4 min/day, over a 12 week open label period. On completion, subjects were offered to enroll into a follow-up study, where the study physicians were given flexibility to alter VNS dosing parameters and/or to add a biologic DMARD to the treatment regimen. DAS28-CRP and Health Assessment Questionnaire-Disability Index (HAQ-DI) were collected over 2 years. Results: All subjects electively continued on VNS treatment through 24 months of the long term follow-up study. Biologic DMARDs were started in 1 and restarted in 8 of 17 subjects; of these, 4 were non-responders to VNS, and 5 had stable improvement but had not yet achieved disease remission on VNS alone (table 1). At the start of the follow-up study, the mean DAS28–28 and HAQ-DI were significantly reduced compared to the pre-implant baseline (mean difference±SE in DAS28-CRP=-1.60±0.37, p<0.0001; mean difference±SE in HAQ-DI = -0.44±0.21, p<0.037), and the depth of effect was retained through 24 months. At 24 months, there was no significant difference in DAS28-CRP between the subjects using VNS monotherapy or those using a combination of VNS and biologic DMARDs (VNS monotherapy= 3.76±1.77 vs. VNS and biologic DMARD= 3.21±1.44, p<0.54). No difference in the adverse events profile between the two groups was seen. Conclusions: The data presented here demonstrate that VNS in subjects with RA is associated with a substantial reduction in disease activity that is sustained for 24 months without untoward safety signals. In addition, the data suggest that biological DMARDs can be initiated safely in combination with VNS treatment, though this requires further study in larger cohorts. These results support further development of VNS devices as an alternative therapeutic approach for RA treatment, which potentially can safely be combined with biologic DMARDs. References: [1]Van Maanen M, et al. The cholinergic anti-inflammatory pathway: towards innovative treatment of rheumatoid arthritis. Nat Rev Rheumatol2009;5:229–32. [2]Koopman FA, et al. Vagus nerve stimulation inhibits cytokine production and attenuates disease severity in rheumatoid arthritis. Proc Natl Acad Sci USA2016;113(29):8284–9. Disclosure of Interest: F. Koopman: None declared, A. Musters: None declared, M. Backer: None declared, D. Gerlag Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, which has an interest in SetPoint, S. Miljko: None declared, S. Grazio: None declared, S. Sokolovic: None declared, Y. Levine Shareholder of: SetPoint Medical, Employee of: SetPoint Medical, D. Chernoff Shareholder of: SetPoint Medical, Adamas Pharmaceuticals, OLLY Nutrition, NAIA Pharma, Aquinox Pharma, Consultant for: Adamas Pharmaceuticals, OLLY Nutrition, NAIA Pharma, Aquinox Pharma, Crescendo BioScience, Employee of: SetPoint Medical, N. de Vries Grant/research support from: Abbvie, Janssen Biologics BV, Ergomed Clinical Research, GlaxoSmithKline, Pfizer, Boehringer Ingelheim, Roche, Consultant for: MSD, Pfizer, P.-P. Tak Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, which has an interest in SetPoint